PERAN TELEPON OPERATOR DALAM MEMBERIKAN PELAYANAN KEPADA TAMU DI MIDTOWN HOTEL SAMARINDA - Dwi Endah Septiani Noordin (Jurnal Inovasi Penelitian, 2022)
The telephone operator at Midtown Hotel Samarinda has the advantage that apart from being a hotel mirror, the telephone operator is also an information center needed for multi-tasking. This study aims to determine the form of telephone operator communication services at Midtown Hotel Samarinda, to determine the role of telephone operator supervisors in serving guests at Midtown Samarinda Hotel, and to determine the role of telephone operator officers in serving guests at Midtown Samarinda Hotel. The author's research method is qualitative, using data analysis from Milles and Huberman (in Sugiyono 2017: 246). The results showed that the role of telephone operators is important to make guests feel satisfied with the services provided by telephone operator staff. Telephone operator supervisors and telephone operator officers have duties and responsibilities to perform. By following standard operating procedures. The communication services provided are in accordance with what is in the hotel's standard operating procedures. Suggestions for telephone operator officers and telephone operator supervisors are expected to be more consistent in providing good service. To make a good impression on guests. The role of telephone operator supervisor is still lacking, because there is no person who is responsible as a supervisor and is delegated to the front office manager.